Diversity, vesicular arbuscular mycorrhizal, oil palm, spores, colonization - Nabilah Nabilah Siregar (Institut Pendidikan Tapanuli Selatan, 2016)
The potential of vesicular arbuscular mycorrhizal as a biological fertilizer can be used to improve soil fertility so the productivity of oil palm tree increase. The first thing that must be known to study the potential of vesicular arbuscular mycorrhizal is to know the diversity of these organisms. Data of diversity vesicular arbuscular mycorrhizal used to obtain the selection of of potential and effective isolates. The aim of this research was to know the density of spore, colonization percentage, and types of vesicular arbuscular mycorrhizal of oil palm tree in PTPN III Batang Toru Estate. The observation chemical of the soil showed that the soil conditions in all of Afdeling are less fertile. The number of spores were found in the field and trapping Afdeling I; 248 and 336 spores/50 g soils respectively in Afdeling III; 225 and 307 spores/50 g soils. Percentage of vesicular arbuscular mycorrhizal colonization in Afdeling I by 42% and Afdeling III 32,7%. Vesicular arbuscular mycorrhizal spores knowed that there consisted of two genera Glomus and Acaulospora.